2015
DOI: 10.17707/agricultforest.61.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Fertilizer Type and Rate, Urease Activity and Total Nitrogen and Ammonium Nitrogen Contents in a Chernozem Soil Under Wheat

Abstract: SUMMARYResearch was conducted on the effects of mineral fertilizers and manure on urease activity and total nitrogen and ammonium nitrogen contents, and their correlation in a chernozem soil during four developmental stages of wheat.The study involved the following treatments: unfertilized control; N2 (100 kg/ha N); P2 (100 kg/ha P); K2 (100 kg/ha K); N2P2; N2K2; P2K2; N1P1K1 (50:50:50 kg/ha); N2P2K2; N3P3K3 (150:150:150 kg/ha), and N1P1K1 + solid manure (20 t/ha). Urease activity was determined by the method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In addition, drip irrigation pipe density can significantly affect the spatial heterogeneity of soil moisture and temperature and the activity of soil enzymes in the crop root-zone; these changes indirectly affect the distribution of crop photosynthetic products [16]. Some studies have reported that plastic-mulching and irrigation management changed soil urease activity [17] and that soil urease regulated nitrogen cycling and increased crop yields [18]. Therefore, different combinations of irrigation volume, plastic covering mode, and drip irrigation pipe density could regulate crop photosynthetic characteristics, both theoretically and practically, thereby affecting photosynthetic product distribution and yield.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, drip irrigation pipe density can significantly affect the spatial heterogeneity of soil moisture and temperature and the activity of soil enzymes in the crop root-zone; these changes indirectly affect the distribution of crop photosynthetic products [16]. Some studies have reported that plastic-mulching and irrigation management changed soil urease activity [17] and that soil urease regulated nitrogen cycling and increased crop yields [18]. Therefore, different combinations of irrigation volume, plastic covering mode, and drip irrigation pipe density could regulate crop photosynthetic characteristics, both theoretically and practically, thereby affecting photosynthetic product distribution and yield.…”
Section: Introductionmentioning
confidence: 99%